Method for preparing oxygen evolution electrode by using mechanical ball milling method

The synthesis of oxygen evolution electrocatalysts at room temperature by mechanical ball milling method solves the problems of high-temperature calcination and few active areas, and realizes batch preparation and performance improvement of high-efficiency oxygen evolution electrocatalysts, simplifies the preparation process and is suitable for commercial applications.

CN119221015APending Publication Date: 2024-12-31SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271188.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the synthesis of black phosphorus/tricobalt tetroxide composite oxygen evolution electrocatalyst requires high temperature calcination, which increases the risk and cumbersomeness of preparation, and its oxygen evolution electrocatalytic performance is not as good as that of nickel and iron catalysts, and traditional nickel and iron metals. There are few active areas of hydroxides and are difficult to regulate.

Method used

Using mechanical ball milling method, catalytic precursors of different chemical elements are synthesized by precipitation control solution and metal salt solution, and mixed modification of specific mechanical ball milling processes to prepare high-efficiency oxygen evolution electrocatalysts, achieving one-step synthesis at room temperature and Cellular and stable chemical composition.

Benefits of technology

The traditional synthesis method has solved the problems of high temperature, harsh reaction conditions, low yield and low interfacial ratio of active surfaces, and achieved the construction of high specific surface area and large-scale catalytic active areas, and improved the activity performance of metal hydroxides such as nickel and iron. , simplifies the preparation process and is suitable for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221015A_ABST
    Figure CN119221015A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing an oxygen evolution electrode by using a mechanical ball milling method, and the method comprises the following steps: S1, dissolving a plurality of transition metal salts respectively to obtain precursor metal salt solutions; respectively dropwise adding the precipitation control solution into the precursor metal salt solution, fully stirring to obtain a precursor suspended deposition solution, filtering and collecting to obtain catalytic precursors of different transition metal ions; and S2, uniformly mixing the obtained catalytic precursors of different transition metal ions, and carrying out mechanical ball milling to obtain the transition metal hydroxide nano-catalyst. By adopting a one-step synthesis method at room temperature, the problems of high temperature, harsh reaction conditions, low yield and high bimetal site codeposition difficulty of a traditional synthesis method are solved, and large-batch preparation of catalytic precursors with uniform and stable chemical components is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalysts, and specifically relates to a method for preparing an oxygen evolution electrode by mechanical ball milling, and in particular to a preparation process for batch preparing high-performance oxygen evolution electrodes by mechanical ball milling. Background Art

[0002] Metal hydroxide nanocatalysts are usually composed of transition metal (nickel, cobalt, iron, etc.) or noble metal (platinum, ruthenium, palladium, etc.) hydroxides and exist at the nanoscale. Metal hydroxide nanocatalysts have the characteristics of high specific surface area and high surface activity. They are easy to modify and have a variety of simple and diverse synthesis methods. Therefore, they can provide more active sites and higher catalytic efficiency. They are widely used in the fields of chemical industry, environmental governance, and energy conversion.

[0003] The existing patent (CN114000174B) discloses a method for preparing a black phosphorus / cobalt tetroxide composite oxygen evolution electrocatalyst. The patent uses the great convenience of mechanical ball milling in the synthesis of large quantities of samples to develop a method for peeling blocky black phosphorus into flakes and compounding them with cobalt tetroxide nanoparticles to prepare a black phosphorus / cobalt tetroxide composite oxygen evolution electrocatalyst. However, the synthesis process of these catalysts requires high-temperature calcination, which greatly increases the danger and complexity of sample preparation, and also produces by-products that are irrelevant to the catalytic process. Moreover, its oxygen evolution electrocatalytic performance is far inferior to that of nickel and iron catalysts. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an oxygen evolution electrode by mechanical ball milling to solve the problems existing in the prior art. The present invention uses a precipitation control solution and a metal salt solution to synthesize a catalytic precursor containing different chemical elements, and uses a specific mechanical ball milling process to mix and modify the catalytic precursor, thereby realizing the batch preparation of high-efficiency oxygen evolution electrocatalysts.

[0005] The purpose of the present invention can be achieved by the following scheme:

[0006] The present invention provides a method for preparing an oxygen evolution electrode by mechanical ball milling, the method comprising the following steps:

[0007] S1. Dissolving a plurality of transition metal salts respectively to obtain a precursor metal salt solution; adding a precipitation control solution dropwise to the precursor metal salt solution, stirring sufficiently, filtering and collecting the precipitate to obtain a catalytic precursor of a plurality of transition metal ions;

[0008] S2. Evenly mix the obtained catalytic precursors of different transition metal ions to obtain a catalyst precursor mixture, and then mechanically ball-mill to obtain a transition metal hydroxide nanocatalyst, namely, an oxygen evolution electrode.

[0009] As an embodiment of the present invention, in step S1, the plurality of transition metals include at least two of Ni, Fe, Co, Mn, and Al. The metal salt includes one or more of nitrate and chloride salts. The purity of the metal salt is greater than 99.9%.

[0010] As an embodiment of the present invention, in step S1, the precipitation control solution includes one or more of sodium borohydride solution, hydrazine hydrate solution, hydroxylamine hydrochloride solution, potassium hydroxide solution, sodium hydroxide solution, etc. The precipitation control solution is a mixture of a precipitation control agent and water.

[0011] As an embodiment of the present invention, in step S1, the concentration of the precursor metal salt solution is 0.1-10 mM, preferably 2-10 mM.

[0012] Preferably, the steps of dissolving the transition metal salt are as follows: weigh the transition metal salt, add ultrapure water to dissolve it, and stir it thoroughly to obtain a precursor metal salt solution.

[0013] As an embodiment of the present invention, in step S1, the concentration of the precipitation control solution is 0.01-5M. The volume ratio of the precursor metal salt solution to the precipitation control solution is 50:20. The mixture of the precipitation control agent and water is alkaline, and the pH value of the solution can be regulated by controlling the content of the precipitation control solution, thereby controlling the generation of the precursor suspension sediment; at the same time, some precipitation control agents have reducing properties, which are helpful to construct low-coordination metal active centers.

[0014] Preferably, the steps for preparing the precipitation control solution are as follows: weigh the precipitation control agent powder for drinking, add ultrapure water to dissolve, stir thoroughly, and obtain the precipitation control solution after no bubbles emerge in the solution.

[0015] As an embodiment of the present invention, in step S1, when the precipitation control solution is added dropwise to the precursor metal salt solution, the pH of the solution is maintained between 12.5 and 13.5.

[0016] As an embodiment of the present invention, in step S1, the stirring temperature is 40-50°C for at least 12 hours, preferably 12-48 hours. The precursor suspension sediment obtained by stirring is filtered to collect the precipitate, which is the catalytic precursor of multiple transition metal ions.

[0017] As an embodiment of the present invention, in step S1, the catalytic precursor collected by filtration is repeatedly washed three times with water and ethanol respectively; and dried in a vacuum drying oven overnight (at least 12 hours) to collect the product.

[0018] As an embodiment of the present invention, in step S2, the proportion of the catalytic precursor of each transition metal ion in the total molar amount of the catalytic precursor mixture is at least 25%. (The molar usage ratio of the catalytic precursor of each transition metal ion is 25%-75%).

[0019] As an embodiment of the present invention, in step S2, the catalytic precursor of transition metal ions is in particle form. The uniform mixing is to mix the catalytic precursor particles of different transition metal ions and grind them thoroughly in a mortar to make the mixture uniform.

[0020] As an embodiment of the present invention, in step S2, the rotation speed of the mechanical ball mill is 200-600 r / min, and the time is 6-48 h.

[0021] As an embodiment of the present invention, in step S2, the transition metal hydroxide nanocatalyst includes one of NiFe, CoFe, NiCo, and NiCoFe metal hydroxide nanocatalysts.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) By adopting a one-step synthesis method at room temperature, the problems of high temperature, harsh reaction conditions, low yield, and difficulty in co-deposition of bimetallic sites in traditional synthesis methods were solved, and large-scale preparation of catalytic precursors with uniform and stable chemical composition was achieved.

[0024] (2) By using mechanical ball milling technology to mix two different substances, the problem of the small active area of ​​traditional nickel-iron, cobalt-iron and other metal hydroxides is solved, a high specific surface area and a large range of catalytic active areas are provided, and the electrochemical synergistic effect of Ni and Fe metal particles on the active interface is fully exerted, and further modification of high-performance nickel-iron metal hydroxides on traditional supporting electrodes is achieved. Compared with the traditional synthesis method of first mixing multiple metal salt solutions and then adding a precipitation control agent to co-precipitate the two metal salt solutions, the present invention first adds precipitation control solutions separately to synthesize a precursor containing only one metal, and then mixes the two and ball mills. The method can be used to synthesize a higher density of high-activity nickel-iron, cobalt-iron and other synergistic structures; at the same time, the rich oxygen defects are directional constructed at the interface where the two metal sites are combined, which helps to regulate the coordination environment and electronic structure of the bimetallic synergistic sites. For nickel-iron metal hydroxide, the Fe site has a smaller oxidation inhibition effect on the Ni lattice site, which is conducive to the formation of active nickel hydroxide species.

[0025] (3) By adopting mechanical ball milling technology, two different metal hydroxides are mixed by mechanical force, and the energy generated by local collision and friction causes the bridging oxygen bonds of the same metal species to break and the bridging oxygen bonds of different species to form, thereby constructing abundant bimetallic synergistic sites at the interface between the two phases, thereby solving the problems of low active surface-to-surface ratio, great construction difficulty and difficulty in regulation of traditional NiFe-based catalysts. High-density active Ni-Fe interfaces are constructed in batches, which are easy to operate and commercially applicable, and realize the batch preparation of gram-level amorphous high-performance metal hydroxide oxygen evolution catalysts and excellent oxygen evolution electrocatalytic performance in anion exchange membrane electrolyzers. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0027] Figure 1 is a flow chart of the preparation process of Example 1 or Example 3 of the present invention;

[0028] Figure 2 The scanning electron microscope images of the catalyst precursor containing Ni and Fe metal ions prepared in Example 1, wherein a is a scanning electron microscope image containing Ni metal ions, and b is a scanning electron microscope image of the catalyst precursor containing Fe metal ions;

[0029] Figure 3 TEM images of the catalytic precursor containing both Ni and Fe metal ions prepared in Example 1, wherein a is a morphological image of the catalytic precursor containing both Ni and Fe metal ions, and b is a HRTEM and selected area electron diffraction image of the catalytic precursor containing both Ni and Fe metal ions;

[0030] Figure 4 This is a scanning electron microscope image of the NiFe metal hydroxide nanocatalyst prepared in Example 1;

[0031] Figure 5 This is a transmission electron microscope image of the NiFe metal hydroxide nanocatalyst prepared in Example 1;

[0032] Figure 6 Electrochemical performance test of NiFe metal hydroxide nanocatalysts prepared in Example 1 and Comparative Examples 1-2 under a three-electrode system;

[0033] Figure 7 The electrochemical performance of the NiFe metal hydroxide nanocatalyst prepared in Example 1 in an anion exchange membrane electrolyzer (AEMWEs) at different temperatures;

[0034] Figure 8is a scanning electron microscope image of the NiFe LDHs metal nanoparticles prepared in Comparative Example 1, wherein a and b are scanning electron microscope images of the NiFe LDHs metal nanoparticles;

[0035] Fig. 9 It is a transmission electron microscope image of NiFe LDHs metal nanoparticles prepared in Comparative Example 1;

[0036] Fig.10 The electrochemical performance of the NiFe metal hydroxide nanocatalysts prepared in Example 1 and Comparative Example 3;

[0037] Fig.11 The electrochemical performance of the NiFe metal hydroxide nanocatalysts prepared in Example 1 and Examples 4-5;

[0038] Fig.12 These are SEM images of metal hydroxide nanocatalysts at different Ni:Fe ratios prepared in Example 2, wherein a is a ratio of 75:25, b is a ratio of 65:35, c is a ratio of 55:45, and d is a ratio of 50:50;

[0039] Fig.13 The electrochemical performance pictures of the metal hydroxide nanocatalysts prepared in Example 2 at different Ni and Fe ratios;

[0040] Fig.14 The electrochemical performance of the CoFe metal hydroxide nanocatalysts prepared in Example 3 and Comparative Examples 4-5 was tested in a three-electrode system. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0042] Example 1 (precipitation → mixing → ball milling)

[0043] This embodiment provides a method for preparing an oxygen evolution electrode using a mechanical ball milling method. Figure 1 As shown, the following steps are included:

[0044] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0045] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0046] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0047] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) to maintain the pH of the mixed solution between 12.5 and 13.5 until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green, filtering and washing the product three times in deionized water and ethanol, and vacuum drying for at least 12 hours to obtain a catalytic precursor containing Ni ions; the scanning electron microscope image is as follows Figure 2 As shown in a, the TEM image is Figure 3 As shown in a;

[0048] (5) Slowly drop the solution obtained in step (1) into the solution obtained in step (3) until the pH value of the solution reaches 13, and stir vigorously during the process; then continue to stir the solution vigorously, control the solution temperature to room temperature, and continue to drop the solution obtained in step (1) to maintain the pH value of the mixed solution between 12.5 and 13.5 until the solution obtained in step (1) is completely dropped, and the mixed solution obtained at this time is black; continue to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown, stop, filter and wash the product three times in deionized water and ethanol, and vacuum dry for at least 12 hours to obtain a catalytic precursor containing Fe ions, and the scanning electron microscope image is as shown Figure 2 As shown in b, the TEM image is Figure 3 As shown in b;

[0049] (6) The catalytic precursors containing Ni and Fe ions obtained in step (4) and step (5) were uniformly mixed in a molar ratio of 65:35, fully ground in a mortar, and then mechanically ball-milled for 24 h to obtain a NiFe metal hydroxide nanocatalyst. The scanning electron microscope image is as follows: Figure 4 As shown in the transmission electron microscope image Figure 5 shown.

[0050] Comparative Example 1 (mixing → precipitation)

[0051] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0052] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 6.5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0053] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 3.5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0054] (4) The solutions obtained in steps (2) and (3) were thoroughly mixed and stirred for 30 min;

[0055] (5) The solution obtained in step (1) is slowly added dropwise to the solution obtained in step (4), and the pH of the solution is controlled to be maintained between 12.5 and 13.5. The mixture is vigorously stirred for at least 12 hours while the solution is added dropwise, and the mixture is stopped when the color of the mixture changes from black to brownish yellow. The product is filtered and washed three times in deionized water and ethanol, and vacuum dried for at least 12 hours to obtain a catalytic precursor containing both Ni and Fe ions. The scanning electron microscope image is as follows: Figure 8 As shown in the transmission electron microscope image Fig. 9 shown.

[0056] Comparative Example 2 (mixing → precipitation → ball milling)

[0057] (6) The catalytic precursor containing both Ni and Fe ions obtained in step (5) of Comparative Example 1 was fully ground in a mortar, and then mechanically ball-milled for 24 h to obtain NiFe LDHs metal nanoparticles.

[0058] Comparative Example 3 (precipitation → mixing)

[0059] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0060] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 6.5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0061] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 3.5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0062] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green;

[0063] (5) slowly adding the solution obtained in step (1) dropwise to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) dropwise to maintain the pH value of the mixed solution between 12.5 and 13.5, until the solution obtained in step (1) is completely added, at which time the obtained mixed solution is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown;

[0064] (6) The product obtained in step (4) and the product obtained in step (5) are fully mixed, stirred for 30 minutes, filtered and washed three times in deionized water and ethanol, and vacuum dried for at least 12 hours to obtain a product.

[0065] Example 2 (Controlling Ni / Fe Ratio)

[0066] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0067] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0068] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0069] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green, filtering and washing the product three times in deionized water and ethanol, and vacuum drying for at least 12 hours to obtain a catalytic precursor containing Ni ions;

[0070] (5) slowly adding the solution obtained in step (1) to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) to maintain the pH value of the mixed solution between 12.5 and 13.5 until the solution obtained in step (1) is completely added, and the mixed solution obtained at this time is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown, and stopping, filtering and washing the product in deionized water and ethanol three times, and vacuum drying for at least 12 hours to obtain a catalytic precursor containing Fe ions;

[0071] (6) The catalytic precursors containing Ni and Fe ions obtained in step (4) and step (5) were uniformly mixed in a mass ratio of 75:25, 65:35 (Example 1), 55:45, and 50:50, fully ground in a mortar, and then mechanically ball-milled for 24 h to obtain NiFe metal hydroxide nanocatalysts. The SEM images of the metal hydroxide nanocatalysts at different Ni:Fe ratios are shown in FIG. Fig.11 shown.

[0072] Example 3 (precipitation → mixing → ball milling)

[0073] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0074] (2) Dissolve cobalt nitrate powder in 50 mL of deionized water to prepare a 5 mM cobalt nitrate solution and stir thoroughly for 30 min;

[0075] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0076] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) to maintain the pH of the mixed solution between 12.5 and 13.5 until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green, filtering and washing the product three times in deionized water and ethanol, and vacuum drying for at least 12 hours to obtain a catalytic precursor containing Co ions;

[0077] (5) slowly adding the solution obtained in step (1) to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) to maintain the pH value of the mixed solution between 12.5 and 13.5 until the solution obtained in step (1) is completely added, and the mixed solution obtained at this time is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown, and stopping, filtering and washing the product in deionized water and ethanol three times, and vacuum drying for at least 12 hours to obtain a catalytic precursor containing Fe ions;

[0078] (6) The catalytic precursors containing Co and Fe ions obtained in step (4) and step (5) were uniformly mixed in a molar ratio of 1:1, fully ground in a mortar, and then mechanically ball-milled for 24 hours to obtain a CoFe metal hydroxide nanocatalyst.

[0079] Comparative Example 4 (mixing → precipitation → ball milling)

[0080] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0081] (2) Dissolve cobalt nitrate powder in 50 mL of deionized water to prepare a 5 mM nickel nitrate solution and stir thoroughly for 30 min;

[0082] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0083] (4) The solutions obtained in steps (2) and (3) were thoroughly mixed and stirred for 30 min;

[0084] (5) Slowly drop the solution obtained in step (1) into the solution obtained in step (4), control the pH of the solution to be maintained between 12.5 and 13.5, and vigorously stir for at least 12 hours while dropping the solution, until the color of the mixed solution changes from black to brown-yellow, filter and wash the product three times in deionized water and ethanol, and vacuum dry for at least 12 hours to obtain a catalytic precursor containing both Co and Fe ions.

[0085] (6) The catalytic precursor containing both Co and Fe ions obtained in step (5) of Comparative Example 4 was fully ground in a mortar, and then mechanically ball-milled for 24 h to obtain CoFe LDHs metal nanoparticles.

[0086] Comparative Example 5 (precipitation → mixing)

[0087] (1) Dissolve sodium borohydride powder in deionized water to prepare 20 mL of 1 M sodium borohydride solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat the process twice;

[0088] (2) Dissolve cobalt nitrate powder in 50 mL of deionized water to prepare a 5 mM nickel nitrate solution and stir thoroughly for 30 min;

[0089] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0090] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green;

[0091] (5) slowly adding the solution obtained in step (1) dropwise to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) dropwise to maintain the pH value of the mixed solution between 12.5 and 13.5, until the solution obtained in step (1) is completely added, at which time the obtained mixed solution is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown;

[0092] (6) The product obtained in step (4) and the product obtained in step (5) are fully mixed, stirred for 30 minutes, filtered and washed three times in deionized water and ethanol, and vacuum dried for at least 12 hours to obtain a product.

[0093] Example 4

[0094] (1) Dissolve a certain volume fraction of hydrazine hydrate solution in deionized water to prepare 20 mL of 0.2 M hydrazine hydrate solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and prepare twice;

[0095] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 6.5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0096] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 3.5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0097] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green;

[0098] (5) slowly adding the solution obtained in step (1) dropwise to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) dropwise to maintain the pH value of the mixed solution between 12.5 and 13.5, until the solution obtained in step (1) is completely added, at which time the obtained mixed solution is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown;

[0099] (6) The product obtained in step (4) and the product obtained in step (5) are fully mixed, stirred for 30 minutes, filtered and washed three times in deionized water and ethanol, and vacuum dried for at least 12 hours to obtain a product.

[0100] Example 5

[0101] (1) Dissolve potassium hydroxide powder in deionized water to prepare 20 mL of 1 M potassium hydroxide solution, stir thoroughly for 30 min until the bubbles in the solution completely disappear, and repeat this process twice;

[0102] (2) Dissolve nickel nitrate powder in 50 mL of deionized water to prepare a 6.5 mM nickel nitrate solution, and stir thoroughly for 30 min;

[0103] (3) Dissolve ferric nitrate powder in 50 mL of deionized water to prepare a 3.5 mM ferric nitrate solution and stir thoroughly for 30 min;

[0104] (4) slowly adding the solution obtained in step (1) to the solution obtained in step (2) until the solution obtained in step (1) is completely added, and the mixed solution obtained is black; continuing to stir vigorously for at least 12 hours until the color of the mixed solution changes from black to gray-green;

[0105] (5) slowly adding the solution obtained in step (1) dropwise to the solution obtained in step (3) until the pH value of the solution reaches 13, and stirring vigorously during the process; then continuing to stir the solution vigorously, controlling the solution temperature to room temperature, and continuing to add the solution obtained in step (1) dropwise to maintain the pH value of the mixed solution between 12.5 and 13.5, until the solution obtained in step (1) is completely added, at which time the obtained mixed solution is black; continuing to stir vigorously for at least 12 hours, until the color of the mixed solution changes from black to reddish brown;

[0106] (6) The product obtained in step (4) and the product obtained in step (5) are fully mixed, stirred for 30 minutes, filtered and washed three times in deionized water and ethanol, and vacuum dried for at least 12 hours to obtain a product.

[0107] Performance Testing:

[0108] All electrochemical tests were performed using a Gamry 3000 electrochemical workstation. Before testing, 20 cycles of CV were performed to activate the catalyst performance with a scan rate of 100 mV s -1 All electrochemical data presented in the figures were obtained using a scan rate of 10 mV s -1 The CV cycle is completed.

[0109] The electrochemical performance of the NiFe metal hydroxide nanocatalyst obtained in Example 1 and the NiFe LDHs metal nanoparticles obtained in Comparative Examples 1-2 under a three-electrode system is tested as follows: Figure 6 shown.

[0110] The electrochemical performance of the NiFe metal hydroxide nanocatalyst obtained in Example 1 in an anion exchange membrane electrolyzer (AEMWEs) at different temperatures is as follows: Figure 7 as shown.

[0111] The electrochemical performance of the catalytic precursor before ball milling and the NiFe metal hydroxide nanocatalyst (Example 1) after ball milling in Comparative Example 3 is as follows: Fig.10 shown.

[0112] The electrochemical performance of metal hydroxide nanocatalysts prepared in Example 2 at different Ni and Fe ratios is shown in the figure below. Fig.12 shown.

[0113] The electrochemical performance of the CoFe metal hydroxide nanocatalysts prepared in Example 3 and Comparative Examples 6-7 under a three-electrode system is tested as follows: Fig.13 shown.

[0114] Table 1 Performance of the products of the embodiments and comparative examples

[0115]

[0116]

[0117] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing an oxygen evolution electrode by mechanical ball milling, characterized in that: The method comprises the following steps: S1. Dissolving a plurality of transition metal salts respectively to obtain precursor metal salt solutions; dropping a precipitation control solution into each precursor metal salt solution, stirring sufficiently, filtering and collecting the precipitate to obtain catalytic precursors of a plurality of transition metal ions; S2. Evenly mix the obtained catalytic precursors of different transition metal ions to obtain a catalyst precursor mixture, and then mechanically ball-mill to obtain a transition metal hydroxide nanocatalyst, namely, an oxygen evolution electrode.

2. The method according to claim 1, characterized in that In step S1, the plurality of transition metals include at least two of Ni, Fe, Co, Mn, and Al; And / or, the metal salt includes one or more of nitrate salt and chloride salt.

3. The method according to claim 1, characterized in that In step S1, the concentration of the precursor metal salt solution is 0.1-10 mM.

4. The method according to claim 1, characterized in that: In step S1, the precipitation control solution includes one or more of sodium borohydride solution, hydrazine hydrate solution, hydroxylamine hydrochloride solution, potassium hydroxide solution, and sodium hydroxide solution.

5. The method according to claim 1, characterized in that In step S1, the concentration of the precipitation control solution is 0.01-5M.

6. The method according to claim 1, characterized in that In step S1, when the precipitation control solution is added dropwise to the precursor metal salt solution, the pH of the solution is maintained between 12.5 and 13.

5.

7. The method according to claim 1, characterized in that In step S1, the stirring temperature is 40-50°C and the stirring time is 12-48 hours.

8. The method according to claim 1, characterized in that In step S2, the proportion of each transition metal ion catalyst precursor in the total molar amount of the catalyst precursor mixture is at least 25%.

9. The method according to claim 1, characterized in that: In step S2, the rotation speed of the mechanical ball mill is 200-600 r / min, and the time is 6-48 h.

10. The method according to claim 1, characterized in that In step S2, the transition metal hydroxide includes one of NiFe, CoFe, NiCo, and NiCoFe metal hydroxides.